Comparative performance study of vapour compression-absorption cascaded system at optimum condensing temperature. (2016) - Jain, Vaibhav; Sachdeva, Gulshan; Kachhwaha, Surendra Singh
The present study thermodynamically analyse a vapour compression-absorption cascaded refrigeration system (CRS) that uses R407C and H2 O-LiBr as refrigerants, to determine the optimal condensing temperature of cascade condenser. The optimum condensing temperature of cascade condenser is found to be 18°C for 83.09 kW refrigeration capacity at an evaporating and condensing temperature of 0.4°C and 46.8°C respectively. The optimum condensing temperature is found, to maximise the rational efficiency of CRS and minimise the total irreversibility of system. Further comparative study of CRS with equivalent vapour compression refrigeration system (VCRS) used for water chilling applications shows that the electric power consumption in CRS is reduced by 70% and COP of compression section is improved by 235% as compared to equivalent VCRS.